2021
DOI: 10.1007/s10775-021-09505-z
|View full text |Cite
|
Sign up to set email alerts
|

In the same boat? An online group career counseling with a group of young adults in the time of COVID-19

Abstract: An online group of career counseling for unemployed young adults during the COVID-19 pandemic was developed. Twelve participants were involved in online group career counseling intervention, based on the Life Design for an inclusive and sustainable future. Results indicated at post-test on increased scores on career adaptability, resilience, future orientation, and propensity to identify inclusive and sustainable actions for the future than pre-test. Overall, the online group career counseling intervention eff… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
27
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 19 publications
(30 citation statements)
references
References 43 publications
2
27
0
1
Order By: Relevance
“…These findings are consistent with Ezegbe et al ( 2018 ) who investigated the effect of digital storytelling on the risk of HIV/AID among students and concluded that digital storytelling has a significant effect on increasing students’ knowledge and understanding of HIV/AID. Santilli et al ( 2022 ) showed that online career counseling increases the scores of unemployed youths in career adaptability, resilience, and orientation. Chen et al ( 2021 ) designed an online career intervention during the Covid-19 pandemic to help Chinese high school students improve career readiness and cope with career decision-making problems and concluded that online intervention considerably increased their career readiness and reduced career decision-making problems.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…These findings are consistent with Ezegbe et al ( 2018 ) who investigated the effect of digital storytelling on the risk of HIV/AID among students and concluded that digital storytelling has a significant effect on increasing students’ knowledge and understanding of HIV/AID. Santilli et al ( 2022 ) showed that online career counseling increases the scores of unemployed youths in career adaptability, resilience, and orientation. Chen et al ( 2021 ) designed an online career intervention during the Covid-19 pandemic to help Chinese high school students improve career readiness and cope with career decision-making problems and concluded that online intervention considerably increased their career readiness and reduced career decision-making problems.…”
Section: Discussionmentioning
confidence: 99%
“…In a study by Santilli et al ( 2022 ), an online career counseling group was created for unemployed youth during the Covid-19 pandemic. Twelve participants participated in online career counseling intervention based on life-design for an inclusive and sustainable future.…”
Section: Introductionmentioning
confidence: 99%
“…Most of the published studies with respect to examining narrative-based approaches fall into the Life Design paradigm (Hirschi & Froidevaux, 2020).The Life Design approach has its foundation on social constructivism's epistemology and acknowledges that career development is highly contextualized and individualized. It emphasizes that all the life spheres that are relevant to that person have to be considered for the constructions of career and life projects (Nota & Rossier, 2015;Santilli et al, 2021). Narratability also plays a significant role in this approach; asking clients to produce micronarratives about how they have developed and constructed their self, identity, and career, promotes new meanings to their difficulties, thus triggering change emancipation processes (Savickas, 2015;Savickas et al, 2009).…”
Section: Evidence Regarding the Effectiveness Of Narrative And Mixed ...mentioning
confidence: 99%
“…With so many transitions taking place in the job market in 2020, 2021, 2022 and going into 2023 we see that people are also hungry to deeply contemplate: what kind of work is going to be more fulfilling, enhancing job satisfaction, improving skill sets, and leading to greater happiness according to Executive Briefing by McKinsey and Company. With over 100,000 career coaches in the United States, it's likely that workers will take advantage of these coaches to examine and assess their competencies and skills, to better understand their interests and life goals, and determine which related industries and organizations are most appealing (Savickas et al, 2009;Lodi et al, 2021;Santilli et al, 2021). People are also thinking about their personal values and how they align with the corporate culture within organizations, hence examining more closely the mission statements, ethics, and policies of companies.…”
Section: Solutions For Three Typical Coaching Clientsmentioning
confidence: 99%